Effect of Tacit and Explicit Knowledge Sharing on Teacher Innovation Capability - Asbari, Masduki; Wijayanti, Laksmi Mayesti; Hyun, Choi Chi; Purwanto, Agus; Santoso, Priyono Budi (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This research aimed to measure the effect of tacit and explicit knowledge sharing on teacher innovation capability mediated by organizational learning. Data collection was done by simple random sampling via electronic to the teacher population in Indonesia. The returned and valid questionnaire results were 781 samples. Data processing used SEM method with SmartPLS 3.0 software. The results of this research showed that explicit knowledge sharing had a positive and significant effect on teacher innovation capability, both directly and through organizational learning mediation, while tacit knowledge sharing had a positive and significant effect on teacher innovation capability through organizational learning mediation. Novelty research was proposing a model for building teacher innovation capability through tacit and explicit knowledge sharing with organizational learning as mediation. This research can pave the way to improve teacher readiness in facing the era of education 4.0.